PENGARUH TIMBUNAN RINGAN MORTAR BUSA PENGGANTI TIMBUNAN BIASA PADA JEMBATAN MENGGUNAKAN KONSTRUKSI STRUKTUR BAJA BERGELOMBANG - Hardiansyah Putra; Susy Kartikasari Ariestianty (Jurnal Jalan-Jembatan, 2022)
Corrugated steel structure consist of three types, i.e. standard (corrugation 152 by 51), deep (corrugation 381 by 140) and super deep (corrugation 500 by 237), but only the standard and deep types that has already produced in Indonesia. The steel structure can be used as a bridge structure in combination with the embankment on the top using common fill material. However, several flyover projects in Indonesia used corrugated steel structures with a span of 22 meters to 26 meters and lightweight foam mortar to replace the common fill. This study was conducted to perceive the effect of the use of lightweight foam mortar on the strength of the structure. The evaluation was carried out by simulating the corrugated steel structure with a span of 22 meters and a thickness of 9 mm either with common fill or lightweight foam mortar using finite element software. Furthermore, the strength parameters for each fill material was calculated refer to the Canadian Highway Bridges Design Code. There are four structural strength parameters that was reviewed, i.e. buckling strength, seam strength, plastic hinge, and displacement. The values of these parameters must be greater than 100% that indicates the force occurs is less than the allowable value, meaning the structure is in a safe condition. The calculation result of each strength parameters by using lightweight foam mortar respectively are 358%, 235%, 458% and 319%. As for that using common fill respectively are 99%, 120%, 37% and 27%. These results show, the application of lightweight foam mortar will increase the value of the structural strength parameters that make the bridge structurally safe. Key words: corrugated steel structure, lightweight foam mortar, common fill, buckling strength, seam strength, plastic hinge, displacement.